Synthesis of Eu3+−doped ZnO/Bi2O3 heterojunction photocatalyst on graphene oxide sheets for visible light-assisted degradation of 2,4-dimethyl phenol and bacteria killing - Shandilya, Pooja; Sudhaik, Anita; Raizada, Pankaj; Hosseini-Bandegharaei, Ahmad; Singh, Pardeep; Rahmani-Sani, Abolfazl; Thakur, Vijay Kumar; Saini, Adesh K. (Elsevier, 2020)
We reported the immobilization of binary heterojunction Eu3+-ZnO/Bi2O3 over the surface of graphene oxide (GO) sheets by precipitation method to compose a visible light drive photocatalyst. The ternary nanocomposites were characterized by different spectral technique like FESEM, FTIR, XRD, XPS, EDX, HRTEM, UV–visible, PL, HPLC and LCMS analysis. The high specific surface area of 106.0 m2g-1 of Eu3+-ZnO/Bi2O3/GO nanocomposites was ascertained by BET adsorption-desorption isotherm. The nano-composite exhibit excellent photo-efficiency for the photodegradation of 2, 4-dimethyl phenol (DMP) under visible region and was almost completely mineralized in 100 min as compared to the bare and binary system. The mineralized products of DMP were analyzed by HPLC and LCMS analysis. The kinetic model suggests the degradation pathway obeys pseudo-first order kinetic. Their antibacterial property were assessed against E. coli bacteria and nearly 90% of gram negative bacteria were killed by using ternary photocatalyst as determined by CFU method. Also, Eu3+-ZnO/Bi2O3/GO nanocomposites possessed significant recycle efficiency up to six consecutive cycles which is beneficial to minimize the tariff. The improved photo-efficiency is due to the extension towards visible region, increase surface area, and high charge separation in ternary heterojunction.
Keywords: Eu3+doped ZnO; Bi2O3; Heterojunction formation; Enhanced photo-catalysis; 2,4-Dimethylphenol degradation; Antibacterial activity